Kompetensi Pedagogik Guru dalam Melaksanakan Standar Proses Kurikulum PAI 2013 Edisi Revisi di SMK PGRI Pekanbaru - Devita Devita; Gusma Afriani (Instructional Development Journal, 2020)
This research is motivated by the implementation of the Revised Edition 2013 PAI Curriculum Process Standard which is still relatively low. Therefore, this study aims to: 1) determine the pedagogical competence of teachers in implementing the Revised Edition 2013 PAI Curriculum Process Standards at SMK PGRI Pekanbaru; and 2) knowing the factors that affect the pedagogical competence of teachers in implementing the Revised Edition 2013 PAI Curriculum Process Standards at SMK PGRI Pekanbaru. This type of research is a descriptive research conducted at SMK PGRI Pekanbaru. The population in this study were 1 teacher in the field of Islamic Religious Education, namely, Mr. Farizal., S.Ag., at SMK PGRI Pekanbaru. In this study, researchers took a saturated sampling technique. The data collection techniques used were observation, questionnaires, tests, and documentation. The data collected was then analyzed using SPSS version 18.00 for Windows. Based on the results of this study, it can be concluded that the pedagogical competence of teachers in implementing the Revised Edition 2013 PAI Curriculum Process Standards at SMK PGRI Pekanbaru is classified as "Good". The factors that affect the pedagogical competence of teachers in implementing the Revised Edition of the 2013 PAI Curriculum Process Standards are: 1) teacher educational background; 2) teachers' experiences in teaching; 3) teacher health; 4) teacher income; 5) educational facilities; 6) discipline in work; and 7) school supervision.